The effect of Holistic Planned Grazing™ on African rangelands: a case study from Zimbabwe. Issue 1 (2nd May 2018) - Peel, Mike; Stalmans, Marc
Abstract : Holistic Planned Grazing™ (HPG) is purported to have positive long-term effects on rangelands, enhancing ecosystem services. Given comparable environmental templates, but different management regimes, vegetation monitoring and landscape function analysis showed the Africa Center for Holistic Management (ACHM) at Dimbangombe had a significantly higher rangeland condition (composition, cover, standing crop and soil health) than adjacent Sizinda (SCR) and Monde (MCR) communal rangelands. Overall grazer density on ACHM is 42% higher than that of SCR (no data for MCR). Finer-scale satellite collar data for ACHM yielded a calculated stocking rate of 0, 55 LSU ha -1 y -1 or 24 590 kg km -2, which constitutes high-density grazing. An energy flow estimate shows that the grazing resource would, on average, not be limiting for livestock on ACHM but limiting on SCR. HPG may include an element where kraals are inserted into degraded rangelands for a short period. Overall, ACHM shows stable perennial composition with smaller tufts significantly closer together. A similar result was visible in SCR where maize yields were visibly higher on kraaled areas than on adjacent untreated fields. HPG yields positive long-term effects on ecosystem services (soils and vegetation) and points to the HPG approach enhancing the sustainability of livestock and wildlife in this environment.